KEPEMIMPINAN SPIRITUAL KH. ABDUL GHOFIR NAWAWI DALAM MENUMBUHKAN KEHIDUPAN MODERASI BERAGAMA - Dian Astutik; Ni’ma M. Al-Habsyi; Fika Magfirah Polamolo (Pascasarjana IAIN Sorong, 2022)
This study aims to uncover the spiritual leadership of a Kyai in fostering religious moderation. The method used is descriptive qualitative with a phenomenological approach with primary and secondary data sources. Data collection techniques are observation, interviews, and documentation. Data analysis techniques consist of data collection, data reduction, data presentation, and drawing conclusions. The results showed that spiritual leadership, K.H. Abdul Ghofir Nawawi, among others, has been implemented at the Salafiyah Syafi'iyah Randangan Gorontalo Islamic Boarding School, namely: attitude honesty of heart in fostering religious moderation, Faimes attitude in fostering religious moderation, and humility in fostering religious moderation